2004
DOI: 10.1111/j.1368-5031.2004.00184.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of prostate-specific antigen relapse in prostate cancer: A European consensus

Abstract: A European Consensus on the management of prostate-specific antigen (PSA) relapse in patients with prostate cancer has been formulated. The key recommendations proposed are that total PSA is the best detection tool for prostate cancer, with free and complexed PSA having a role in the PSA range 1-4 ng/ml. PSA relapse after radical prostatectomy (RP) has been defined as a value of 0.2 ng/ml with one subsequent rise, while the ASTRO definition should be used after radiotherapy. A PSA level of less than 0.4 ng/ml … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
15

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 77 publications
(117 reference statements)
0
81
0
15
Order By: Relevance
“…In 2007, the American Urological Association Prostate Guideline Update Panel reviewed 53 different definitions of BCR after RP and recommended using a serum PSA level >0.2 ng/ml, with a second confirmatory level above 0.2 ng/ml to define recurrence [12]. This recommendation is similar to the definition proposed by a European Consensus committee in 2004 [13].…”
Section: Definitions Of Biochemical Recurrencementioning
confidence: 99%
“…In 2007, the American Urological Association Prostate Guideline Update Panel reviewed 53 different definitions of BCR after RP and recommended using a serum PSA level >0.2 ng/ml, with a second confirmatory level above 0.2 ng/ml to define recurrence [12]. This recommendation is similar to the definition proposed by a European Consensus committee in 2004 [13].…”
Section: Definitions Of Biochemical Recurrencementioning
confidence: 99%
“…Median follow-up time was 82 months (range, 10-135). PSA relapse was defined as two consecutive values of 0.2 ng/mL or greater (19). Radiologic progression was defined as the progression in soft tissue lesions measured by computed tomography or MRI, or by progression to bone (20).…”
Section: Patients and Samplesmentioning
confidence: 99%
“…One of commonly used definitions has been PSA ≥0.2 ng/mL with one subsequent rise. The American Urological Association and the European Association of Urology put forward a guideline that recommended PSA ≥0.2 ng/mL with a second confirmatory level of >0.2 ng/mL as the definition of PSA relapse (13)(14)(15). Freeland suggested PSA >0.2 ng/mL as an appropriate cut-off for PSA relapse, and reported that the likelihood of further PSA progression was 86% at 1 year and 100% at 3 years, when a post-operative PSA was >0.2 ng/mL (12).…”
Section: E F I N I T I O N a N D P R E V A L E N C E O F P S A R E mentioning
confidence: 99%